Cyber security awareness: Is there any significant difference in demographic factors? - Sharkawi, Ismawati; Kapong, Joyce Morris; Md Saad, Juniza; Alan, Ribka; Latip, Malisah (Academic Inspired Network, 2023)
The COVID-19 pandemic has changed our daily lives with heavy reliance on digital platforms. The increase in cyber fraud cases is correlated with the rapid adoption of online platforms. Using convenience sampling, this study on 174 responses acquired via an online survey aims to identify the level of awareness of cyber security and to investigate the differences in selected demographic factors including gender, age, and education levels to better comprehend the awareness level of cyber security. While the findings showed that the level of awareness of cyber security is generally high, respondents appeared to show a low level of awareness of whom to refer to in the event of cyber threat and the ability to monitor the use of social media to avoid cyber threats. In addition, results from the Mann-Whitney U test and Kruskal-Wallis test revealed that none of the demographic factors showed any significant difference in the level of awareness. Therefore, the awareness campaign on cyber security should be enhanced to continue raising the public’s level of awareness in general regardless of gender, age, and education level.